MAKTABGACHA YOSHDAGI BOLALARNI ASOSIY GIMNASTIKA VOSITALARI ORQALI KOORDINATSION RIVOJLANTIRISH - Toylibaev, S.M.; Allambergenova, R.D. (SCIENCE and SOCIETY, 2023)
The article talks about the development of motor skills in preschool children by means of basic gymnastics. Also, attention is paid to the structure and basic training of preschool children's motor activity for sports by means of basic gymnastics of a coordinating and developing orientation.
Keywords: preschool children; facilities basic gymnastics; coordination development; degree of physical development; age stages